Circumpolar Mapping of Ground-Fast Lake Ice - Bartsch, Annett; Pointner, Georg; Leibman, Marina O.; Dvornikov, Yuri A.; Khomutov, Artem V.; Trofaier, Anna M. (Frontiers in Earth Science, 2017)
Shallow lakes are common across the entire Arctic. They play an important role as methane sources and wildlife habitats, and they are also associated with thermokarst processes which are characteristic of permafrost environments. Many lakes freeze to the ground along their rims and often over the entire extent during winter time. Knowledge on the spatial patterns of ground-fast and floating ice is important as it relates to methane release, talik formation and hydrological processes, but no circumpolar account of this phenomenon is currently available. Previous studies have shown that ground-fast ice can easily be detected using C-band Synthetic Aperture Radar (SAR) backscatter intensity data acquired from satellites. A major challenge is that backscatter intensity varies across the satellite scenes due to incidence angle effects. Circumpolar application therefore requires the inclusion of incidence angle dependencies into the detection algorithm. An approach using ENVISAT ASAR Wide Swath data (approximately 120 m spatial resolution) has therefore been developed supported by bathymetric measurements for lakes in Siberia. This approach was then further applied across the entire Arctic for late winter 2008. Ground-fast ice fraction has been derived for (1) two million lake objects larger than 0.025 km² (post-processed GlobeLand30), (2) a 50 x 50 km grid and (3) within certain zones relevant for climate studies (permafrost type, last glacial maximum, Yedoma). Especially lakes smaller than approximately 0.1 km² may freeze completely to the ground. The proportion of ground-fast ice increases with increasing soil organic carbon content in the proximity of the lakes. This underlines the importance of such lakes for emission studies and the need to map the occurrence of ground-fast lake ice. Clusters of variable fractions of ground-fast ice occur especially in Yedoma regions of Eastern Siberia and Alaska. This reflects the nature of thaw lake dynamics. Analyses of lake depth measurements from several sites suggest that the used method yields the potential to utilize ground-fast lake ice information over larger areas with respect to landscape development, but results need to be treated with care, specifically for larger lakes and along river courses.